In-situ tissue regeneration through SDF-1α driven cell recruitment and stiffness-mediated bone regeneration in a critical-sized segmental femoral defect. (15th September 2017) - Cipitria, Amaia; Boettcher, Kathrin; Schoenhals, Sophia; Garske, Daniela S.; Schmidt-Bleek, Katharina; Ellinghaus, Agnes; Dienelt, Anke; Peters, Anja; Mehta, Manav; Madl, Christopher M.; Huebsch, Nathaniel; Mooney, David J.; et al.
Graphical abstract: Abstract: In-situ tissue regeneration aims to utilize the body's endogenous healing capacity through the recruitment of host stem or progenitor cells to an injury site. Stromal cell-derived factor-1α (SDF-1α) is widely discussed as a potent chemoattractant. Here we use a cell-free biomaterial-based approach to (i) deliver SDF-1α for the recruitment of endogenous bone marrow-derived stromal cells (BMSC) into a critical-sized segmental femoral defect in rats and to (ii) induce hydrogel stiffness-mediated osteogenic differentiation in-vivo. Ionically crosslinked alginate hydrogels with a stiffness optimized for osteogenic differentiation were used. Fast-degrading porogens were incorporated to impart a macroporous architecture that facilitates host cell invasion. Endogenous cell recruitment to the defect site was successfully triggered through the controlled release of SDF-1α. A trend for increased bone volume fraction (BV/TV) and a significantly higher bone mineral density (BMD) were observed for gels loaded with SDF-1α, compared to empty gels at two weeks. A trend was also observed, albeit not statistically significant, towards matrix stiffness influencing BV/TV and BMD at two weeks. However, over a six week time-frame, these effects were insufficient for bone bridging of a segmental femoral defect. While mechanical cues combined with ex-vivo cell encapsulation have been shown to have an effect in the regeneration of less demanding in-vivo models, such as cranial defects of nude rats, they are not sufficient for a SDF-1α mediated in-situ regeneration approach in segmental femoral defects of immunocompetent rats, suggesting that additional osteogenic cues may also be required. Statement of Significance: Stromal cell-derived factor-1α (SDF-1α) is a chemoattractant used to recruit host cells for tissue regeneration. The concept that matrix stiffness can direct mesenchymal stromal cell (MSC) differentiation into various lineages was described a decade ago using in-vitro experiments. Recently, alginate hydrogels with an optimized stiffness and ex-vivo encapsulated MSCs were shown to have an effect in the regeneration of skull defects of nude rats. Here, we apply this material system, loaded with SDF-1α and without encapsulated MSCs, to (i) recruit endogenous cells and (ii) induce stiffness-mediated osteogenic differentiation in-vivo, using as model system a load-bearing femoral defect in immunocompetent rats. While a cell-free approach is of great interest from a translational perspective, the current limitations are described.